Medical and dental student knowledge about COVID-19 and influenza vaccines impact opinions about vaccine advocacy and future practice - Lucia, Victoria C.; Mascarenhas, Ana Karina; Kelekar, Arati; Afonso, Nelia M. (Frontiers in Public Health, 2024)
Introduction The World Health Organization has identified vaccine hesitancy as a global public health challenge. Healthcare providers are among the most influential and trusted figures for vaccine counseling. This article focuses on COVID-19 and influenza personal immunization behaviors, vaccine knowledge and opinions, and vaccine counseling confidence among future healthcare providers – dental and medical students. Methods A cross-sectional anonymous online survey was conducted at four dental schools and one allopathic medical school in the United States. Items included personal vaccination status for the COVID-19 and influenza vaccines and vaccine-specific items developed based on past research to assess knowledge, opinions, and behaviors. Results Two hundred and thirty-two medical and 221 dental students completed the survey. 68 and 55% scored average/above-average knowledge on COVID-19 and influenza vaccine items, respectively. There were significant differences between those with average/above-average and below-average knowledge scores regarding learning about, recommending, and advocating for vaccines and counseling vaccine-hesitant patients for both vaccines (p < 0.0001). Although higher-knowledge students had higher vaccination rates (p < 0.0001), many had insufficient knowledge about vaccines. Discussion Healthcare providers play a crucial role in vaccine advocacy. The identified knowledge gaps are significant as they impact quality of patient care. And opinions about future vaccination practice such as recommending, providing, and counseling about vaccines. Equipping students with knowledge and communication skills will enable them to be strong vaccine advocates to improve overall public health.